2018
DOI: 10.1371/journal.pone.0203403
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the viral genome between HPV-positive cervical and oropharyngeal cancer

Abstract: Human papillomavirus (HPV)-driven oropharyngeal cancer incidence in the United States has steadily increased in the past decades and has now become the most frequently diagnosed HPV-associated cancer type, surpassing cervical cancer. Variations in the HPV genome correlate with tumorigenic risk, and the distribution of genetic variants is extensively studied in cervical cancer, but very little is known about new mutations or the distribution of HPV types and variants in oropharyngeal cancer. Here we present an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
2
35
1
3
Order By: Relevance
“…This discrepancy probably reflects socio-economic differences between the catchment areas of the two hospitals. In a recent study, HPV type 35 was found as the 2 nd most dominant HPV type in OPC tumours in USA [29], which is different from ours, probably geographic, ethnicity differences that contribute to the discrepancy.…”
Section: Discussioncontrasting
confidence: 87%
“…This discrepancy probably reflects socio-economic differences between the catchment areas of the two hospitals. In a recent study, HPV type 35 was found as the 2 nd most dominant HPV type in OPC tumours in USA [29], which is different from ours, probably geographic, ethnicity differences that contribute to the discrepancy.…”
Section: Discussioncontrasting
confidence: 87%
“…The E7 L28F substitution, which is characteristic for A5 variants, was previously identified in Japanese sex workers [42], and was also reported from Thailand [33] and northeast China [43]. A more recent study also described the same E7 substitution in one oropharyngeal cancer case in the United States [44]. To date, however, the complete genome sequence of a virus harboring the E7 L28F substitution has only been reported for one isolate in Thailand [33].…”
Section: Discussionmentioning
confidence: 73%
“…Cervical cancer (CC), the third most prevalent cancer in women ( 7 ), is an HPV-related disease for which the burden is the most blatant, as it leads to high mortality in women after breast cancer ( 8 ). Overall, the epidemiologic distribution of HPV infection and HPV-associated burden vary significantly across the world, and the morbi-mortality–associated factors include geographic, socioeconomic, cultural, and genetic factors related to viral genome variability as well as intrinsic individual factors such as age, gender, anatomic site, and health state ( 9 ). The three types of currently approved HPV vaccines, including bivalent, tetravalent, and 9-valent vaccines, are effective in reducing HPV infection and HPV-related disease incidence, as reported in several world regions.…”
Section: Introductionmentioning
confidence: 99%